MEKANISME SISTEM PERADILAN MILITER DALAM PENANGANAN PERKARA TINDAK PIDANA UMUM YANG DILAKUKAN OLEH PRAJURIT TNI DI INDONESIA - Karso; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Soldiers of the Indonesian National Armed Forces (TNI) are members of the Indonesian National Armed Forces (TNI) ranging from Private to General, representing the ranks of Private, Non-commissioned Officer, and Officer, who constitute a military unit. TNI soldiers are often faced with criminal cases, requiring them to face military justice. The Indonesian legal system has established a military-style mechanism for TNI soldiers who commit general crimes, based on the principle of equality before the law and legal certainty, based on the grounds for the charges against active TNI soldiers, namely Law Number 31 of 1997 concerning Military Justice and the Military Criminal Code (KUHPM). This is also based on the provisions of Article 65 paragraphs (1) and (2) of Law Number 34 of 2004 concerning the TNI, which strengthens the legal position of military justice as an institution with special expertise in military law. This research uses a normative juridical method with a regulatory-legal approach, a contextual approach, and a literature review to examine the legal basis, legal impact, and regulations regarding the legal accountability mechanism for TNI soldiers in the military justice system, as well as the relevance of training to soldier discipline and professionalism. The findings indicate that in addition to criminal penalties, soldiers can also be subject to administrative sanctions in the form of Dishonorable Discharge (PTDH), which has consequences for social status and administrative rights.